STRATEGI KOMPETENSI KOMUNIKASI ANTAR BUDAYA MASYARAKAT PESISIR PANTAI DI KEPULAUAN SERIBU JAKARTA - Agustina Zubair (Universitas Mercu Buana, 2019)
Tourism is an important commodity for Indonesia, for several reasons, in addition to geographical reasons, namely Indonesia has the world's fourth longest coastline, cultural diversity, and other potential. In the face of the Asean Economic Community (AEC), each country will then compete with each other while supporting each other to face global competition. The aim of the research is to answer the problem, namely to determine the competence of intercultural communication and the development of tourism in coastal areas. To that end, researchers try to explain the research objectives, namely to find out the competency strategies of intercultural communication among coastal communities in the Thousand Islands, Jakarta and to find out coastal communities in the face of changes that tourism in the Thousand Islands, Jakarta is increasingly developing. This research uses a constructivist paradigm. The theory used in this study is the communication competency strategy of Charles Berger that can be used to gather information and reduce the level of uncertainty. This research method uses a case study with a qualitative approach and uses triangulation for data validity techniques.